Research on innovative preparation and performance of semi flexible pavement materials - Chen Songqiang; Zhou Jian; Wu Xi; Chen Zining (Case Studies in Construction Materials, 2024)
Semi-flexible concrete has been utilized in highway engineering due to its exceptional pavement performance. This study investigates the proportions of semi-flexible grout, the porosity of asphalt mixture, and the performance of semi-flexible concrete. Initially, 18 sets of semi-flexible grouting materials were proposed through an orthogonal test, resulting in the following material ratio: (cement: mineral powder): water cement ratio: sand cement ratio: Swelling agent: water reducer: flocculant = (0.85:0.15):0.45:0.2:0.04:0.001:0.005. Subsequently, the impact of the 2.36 mm sieve passing rate on the air void of SFAC-13 and SFAC-16 mixtures was analyzed, and a relationship between them was established. Observation of the semi-flexible concrete section and analysis of the grouting rate indicated that the developed grouting material effectively fills the gaps in the asphalt mixture. Lastly, the pavement performance of semi-flexible concrete was compared with SMA-13 asphalt mixture. The results demonstrate that semi-flexible composite concrete exhibits outstanding dynamic modulus, crack resistance, deformation resistance, water stability, and low-temperature performance. Moreover, the material properties of SFAC-13 are akin to those of SFAC-16.